Exploring the Anti-Inflammatory Potential of Ethyl Acetate Extract of Lobophytum sp. from Southeast Sulawesi Sea - Adryan Fristiohady; Diasty Nuraisya; Lidya Agriningsih Haruna; Parawansah Parawansah; Agung W.M. Yodha; La Ode Muhammad Julian Purnama; Sahidin Sahidin; Rathapon Asasutjarit; Muhammad Hajrul Malaka (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2025)
Compounds derived from marine organisms have gained significant interest for their potential therapeutic effects on inflammatory diseases. Lobophytum sp., a soft coral species, has demonstrated anti-inflammatory properties by inhibiting the production of TNF-α and IL-1β, two crucial cytokines involved in the inflammatory process. This study assessed the anti-inflammatory potential of the ethyl acetate extract of Lobophytum sp. (LEA) using in vivo models. The extract was obtained through maceration using ethyl acetate.  Phytochemical screening identified various bioactive compounds, including flavonoids, alkaloids, and terpenoids, known for their ability to modulate various biological pathways. To evaluate the anti-inflammatory effects, LEA was tested in a mouse model of xylene-induced ear edema, a common assay for inflammation. Diclofenac sodium, a well-known anti-inflammatory drug, was used as a positive control. LEA was administered at a dose of 0.05, 0.1, and 0.2 mg.mL-1. The results revealed that LEA significantly reduced the swelling of the ear and suppressed the release of key pro-inflammatory cytokines, such as TNF-α and IL-1β. The expression levels of IL-1β and TNF-α were measured using the ELISA reader method. These findings suggest that the anti-inflammatory effects of LEA are likely mediated by the modulation of inflammatory signalling pathways, potentially involving the inhibition of cytokine production. The most effective dose in this study was 0.1 mg.mL-1. Overall, the results highlight the promising therapeutic potential of LEA as a natural anti-inflammatory agent. Further investigation is needed to explore the underlying mechanisms of action and evaluate its clinical applications for treating inflammatory diseases.